Recombinant-enzyme fermentation - Amid, Azura; Ismail, Nurul Azira; Jamaluddin, Mohd Jamil Aizat (Springer International Publishing, 2015)
This chapter presents an overview of the issues involved in the fermentation of E. coli harboring a transgene. The successful production of a heterologous enzyme requires the thoughtful integration and optimization of media formulations, physical factors associated with fermentation, host specificities and induction strategies.